Perancangan UI/UX dengan Metode Design Thinking Pada Shoekuna Shoe Laundry Berbasis Mobile - Aulia, Sarah; Syahidin, Yuda (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Shoe laundry services began to develop and became popular in various big cities in Indonesia in 2014. The laundry workers took an opportunity to see the community's enthusiasm for their interest in caring for shoes. Business people see shoe owners as busy, so they don't have much time to take care of their shoes. At the same time, people generally need shoes for daily activities such as the world, school, or work. With the increasing number of shoe washing service businesses, actors in this field are competing to attract potential consumers with the latest innovations constantly being developed. Therefore, business people in this field continue to make sales to turn potential consumers into consumers of their services by using technological innovations to make them even better. This study will design the shoe washing android application's user interface and user experience to help run this business. The method used in this research uses Design Thinking. Based on the results of the interviews, a prototype design was made and then tested by user respondents and gave a score of 6 out of 7 with the conclusion that respondents were satisfied and helped by this solution design.